Basal slip of ⟨a⟩ screw dislocations in hexagonal titanium. (15th March 2019) - Kwasniak, Piotr; Clouet, Emmanuel
Abstract: Basal slip of ⟨ a ⟩ screw dislocations in hexagonal closed-packed titanium is investigated with ab initio calculations. We show that a basal dissociation is highly unstable and reconfigures to other structures dissociated in a first order pyramidal plane. The obtained mechanism for basal slip corresponds to the migration of the partial dislocations and of the associated stacking fault ribbon in a direction perpendicular to the dissociation plane. Presented results indicate that both basal and pyramidal slip will operate through the Peierls mechanism of double-kink nucleation and will be equally active at high enough temperature. Graphical Abstract: